Socio-political and poetic reality of resistance among Romanian women authors: the case of Oana Orlea (Colloquia Comparativa Litterarum, 2025)
The writings of Oana Orlea reflect a troubled historical period in her native country, Ceauşescu’s Romania, and a painful personal experience lived within this historical context. Situated on an uncertain boundary between referentiality and fictionality, the novel Un sosie en cavale creates a space of resistance to oppressive power structures, a refuge where personal memories are intertwined with historical and cultural reminiscences. Both through her autobiographical narrative Les années volées and her novel, the author is part of the intellectual community that asserts the duty to bear witness, so that future generations may understand the marks of totalitarianism on both the individual and society.
Keywords: resistance literature; totalitarian regime; Balkans; violence; memory